Newly paired zebra finches have higher dopamine levels and immediate early gene Fos expression in dopaminergic neurons. Issue 12 (8th October 2013) - Banerjee, Sunayana B.; Dias, Brian G.; Crews, David; Adkins‐Regan, Elizabeth
Abstract Most birds are socially monogamous, yet little is known about the neural pathways underlying avian monogamy. Recent studies have implicated dopamine as playing a role in courtship and affiliation in a socially monogamous songbird, the zebra finch (Taeniopygia guttata). In the present study, we sought to understand the specific contribution to pair formation in zebra finches of the mesolimbic dopaminergic pathway that projects from the midbrain ventral tegmental area to the nucleus accumbens. We observed that paired birds had higher levels of dopamine and its metabolite 3, 4‐dihydroxyphenylacetic acid in the ventral medial striatum, where the nucleus accumbens is situated, than unpaired birds. Additionally, we found that the percentage of dopaminergic neurons expressing immediate early gene Fos, a marker of neuronal activity, was higher in the ventral tegmental area of paired birds than in that of unpaired birds. These data are consistent with a role for the mesolimbic dopaminergic pathway in pair formation in zebra finches, suggesting the possibility of a conserved neural mechanism of monogamy in birds and mammals.